Mothers of Srebrenica: Causation and Partial Liability under Dutch Tort Law - Rijnhout, Rianka (Utrecht Journal of International and European Law, 2021)
This article explains the Dutch theory of partial liability and why the application of this theory benefited the plaintiffs in the case of Mothers of Srebrenica from a tort law perspective. Partial liability is a theory under Dutch law to redeem causal uncertainties, and therefore functions as an exception to the main rule of sufficient degree of proof of a condicio sine qua non (CSQN) between the wrong and the damage, justified by legal justice and reasonableness. Loss of a chance is one variation of partial liability and was applied in the case Mothers of Srebrenica. The theory of lost chance essentially makes it possible to establish liability to a proportion, notwithstanding the causal uncertainty between the wrong and the original damage which would have resulted in a denial of the claim under tort law.